EFFECT OF PLANTING METHODS ON YIELD AND ECONOMICS OF POTATO UNDER NORTH GUJARAT CONDITIONS - Patel, C. K.; Sasani, G. V.; Patel, R. N; Chaudhari, S. M.; Patel, N. H.; Vihol, K. J. (Potato Journal, 2013)
An experiment was conducted during rabi seasons of 2001-02 to 2003-04 on light textured soils at potato research station, Deesa in randomized block design with three treatments replicated six times. The cut seed tubers of 30 g (+5 g) size of potato cv. Kufri Badshah were planted at the spacing of 50 x 20 cm in bullock drawn single row deshi plough, 45 x 20 cm in tractor drawn single row planter, while in case of tractor drawn paired row planting, the ridge and furrow width was 75 cm each and two rows of potato crop was raised on each ridge at 20 x 20 cm spacing. The significantly higher total tuber yield of potato (393 q/ha) was recorded under the tractor drawn single row planting followed by bullock drawn single row deshi plough (326 q/ha) planting method. Tractor drawn single row planting produced 20.51 and 30.59% higher tuber yield over bullock drawn single row deshi plough and tractor drawn paired row planting method, respectively. Considering the economics of the different methods, the highest net return of Rs.81,290 per ha and B:C ratio (2.45) were recorded by tractor drawn single row planting method. It also saved manpower at planting time and covered more area per unit time.